Timeliness for Submitting Financial Statements to Mining Companies in Indonesia - Ernanda, Mercedes Daimler Benz; Charis, Charis; Pratiwi, Monica Weni (AIBPM Publisher, 2022)
The purpose of this study to find out empirically the effect of firm size on the timeliness of the submission of financial statements, with profitability as a moderating variable. This study uses a quantitative approach using secondary data. The sample was selected by purposive sampling from a population of mining sector companies listed on the IDX starting in 2019 – 2021. The hypothesis was tested using the SPSS program with the moderated regression analysis technique. The results of the study indicate that the size of the company doesn’t have affects to the timeliness of the submission of financial statements, and profitability does strengthen or weaken the effect of the size of the company on the timeliness of the submission of financial statements. Based on the research results, further research can add company age. Based on the results of the study, further research can add the variable age of the company. Because age is a consideration for investors when investing their capital, companies with an older age develop skills in collecting, processing, and producing information when needed. Then the age of the company will increasingly have an impact on the timeliness of submitting financial statements.Keywords: Firm Size, Mining Companies, Profitability, Submission of Financial Statements, and Timeliness.